METOPROLOL COMPARED TO AMLODIPINE IMPAIRS MITOCHONDRIAL FUNCTION IN FOREARM SKIN IN HYPERTENSIVE PATIENTS. (April 2021) - Pawlak-Chomicka, Regina; Uruski, Pawel; Krauze, Tomasz; Markowska, Malgorzata; Tykarski, Andrzej; Guzik, Przemyslaw
Abstract : Objective: If oxygen is available, then mitochondria oxidase the reduced form of nicotinamide adenine dinucleotide (NADH) and produce energy. Oxygen delivery to mitochondria in skin cells depends on the function of microvascular circulation. Antihypertensive medications can modify both energy metabolism (e.g. gain of body weight) and microvascular function (cold fingers and toes). In this prospective study, we compared the effects of amlodipine vs metoprolol on the skin content of NADH in hypertensive patients. Design and method: Patients with newly diagnosed hypertension were randomly allocated to the six-week treatment with either 5 mg of amlodipine (20 patients) or 25 mg of metoprolol (17 patients) once a day. The 460-nm forearm skin fluorescence measured the skin mitochondrial content of NADH at rest, during transient 100-second ischaemia (by occlusion of the brachial artery with the inflated arm blood pressure cuff), and the following reperfusion. This measurement was made before and after the treatment initiation. Results: Hypotensive effects of both treatment were comparable after the six-week therapy. For NADH, amlodipine showed no significant change in the 460-nm fluorescence at rest (791.6 ± 281.1 to 733.7 ± 261.9 [kU] (p = 0.119), during ischemia (850.2 ± 292.2 to 805.6 ± 294.8 [kU] (p = 0.307), and reperfusion (662.3 ± 228.4 to 624.1 ± 225.0 [kU] (p = 0.210). In contrast, treatment with metoprolol significantly increased the 460-nm fluorescence at rest (678.2 ± 284.0 to 797.3 ± 247.0 [kU] (p < 0.01), during ischemia (736.5 ± 302.1 to 859.7 ± 264.9 [kU] (p < 0.01), and reperfusion (571.5 ± 243.2 to 662.2 ± 204.7 [kU] (p < 0.01). Conclusions: Metoprolol significantly impairs the function of skin mitochondria, causing a significant increase in the NADH content. In contrast, amlodipine shows neutral effects on this function.